PREPARATION OF MUSSEL MEAT BY DRYING - NAIR, T. S UNNIKRISHNAN; MURALEEDHARAN, V; JOSEPH, K GEORGE (Fishery Technology, 2017)
The paper describes a simple and cheap process for the preservation of mussel meatby drying. The method involves blanching the mussel meat shucked from purified live mussels in 5% boiling brine for 5 min followed by drying to a moisture of 10 to 15%. The product stored in glass bottles or polythene bags suitably sealed, has a storage life of about six months after which the organoleptic qualities begin to deteriorate. No preservative is used at any stage of processing and the yield of the product is approximately 20%. The major type of spoilage during storage is brown discoloration. Spoilage due to insect infestation is also common unless packed properly.